"Strong Research Performers” vs. “Strong Teaching Performers” in European Higher Education: a Comparative Quantitative Perspective - Kwiek, Marek (My University, 2014)
Teaching and research are still the two fundamental dimensions of the academic enterprise, despite the increasing role of various, as they are termed in Europe, “third mission activities” (Kwiek 2013). Few academic studies of the academic profession have addressed the nexus of teaching and research from a consistently quantitative perspective. Most comparative studies available until recently were either focused on a small cluster of countries or based on qualitative material combined with publicly available statistical data. At a European level, studies were either of a general nature and based on often incompatible national methodologies, or referred to rela-tively simple, aggregated data produced by the OECD or the EUROSTAT, the European Commission’s statistical office. This paper explores the teaching/research nexus in European systems through large-scale comparative data on the research and teaching time allocation (academic behaviors) and teaching or research role orientation (aca-demic attitudes).
Keywords: young academics; European universities; European academic profession; teaching and research; time distribution; academic attitudes; quantitative approach; CAP study